2018
DOI: 10.1002/cppb.20085
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC‐MS Analyses of Plant Flavonoids

Abstract: Flavonoids are a class of specialized metabolites found in many different plant species. They protect against UV radiation, scavenge reactive oxygen species, are involved in plant defense responses, and are associated with plant‐microorganism interactions. They have also been reported to possess health‐promoting effects including anti‐inflammatory, antioxidant, anticancer activity, and antihypertensive effects. Flavonoids encompass >10,000 structures where the types and amounts depend on the plant species, dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Flavonoids biosynthesis pathway has been extensively studied 51 , 52 . In G. biloba , several transcription factors were cloned and identified to be involved in biosynthetic pathway of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids biosynthesis pathway has been extensively studied 51 , 52 . In G. biloba , several transcription factors were cloned and identified to be involved in biosynthetic pathway of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, flavonoids play an important role in various plant physiological or developmental functions, as well as in the agronomic and industrial qualities of plant products ( Lepiniec et al, 2006 ; Li et al, 2018 ). Numerous studies have found that flavonoids have antioxidant, anti-inflammatory, antimicrobial, anti-fungal, antiviral, anti-tumor properties, and also help to scavenge free radicals and stabilize the reactive oxygen species; these keep the body safe from chronic diseases, such as cancer, diabetes, and cardiovascular and heart disease, enhance the immune system, for example, suppress pro-inflammatory immune response, in particular auto-reactive T cells ( Havsteen, 2002 ; Verbeek et al, 2004 ; Falcone Ferreyra et al, 2012 ; Mouradov and Spangenberg, 2014 ; Lei et al, 2019 ; Sarbu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the vegetable kingdom, flavonoids are reported to play a significant role in plant resistance, both in terms of abiotic and biotic stresses (Nayak et al, 2015), such as drought, UV radiation, and heavy metal contamination (Izaguirre et al, 2007;Lei et al, 2019). In addition to their function in abiotic stress resistance, flavonoids have also been found to be involved in plant protection.…”
Section: Introductionmentioning
confidence: 99%